Epididymitis: ascending infection restricted by segmental boundaries. Issue 7 (20th May 2015) - Stammler, A.; Hau, T.; Bhushan, S.; Meinhardt, A.; Jonigk, D.; Lippmann, T.; Pilatz, A.; Schneider-Hüther, I.; Middendorff, R.
Abstract: STUDY QUESTION: Is the regionalization of epididymitis related to epididymal segmentation? SUMMARY ANSWER: We show for the first time that luminal ascent of bacteria is strictly gated by epididymal segment boundaries, involving ductal constriction adjacent to the infected area. WHAT IS KNOWN ALREADY: The epididymal duct is a continuous, unbranched tube, coiled into segments that are divided by connective tissue septa. Sonographic analysis indicates that swelling associated with epididymitis is predominant in the cauda region. Epididymal segmentation has never been investigated in the context of pathological alterations. STUDY DESIGN, SIZE, AND DURATION: We analyzed segment-specific changes in the epididymal duct in a mouse model and in men. In the mouse epididymitis model (3 days post-infection, injection of bacteria into the lumen of the vas deferens), two Escherichia coli strains were tested: a uropathogenic strain CFT073 (UPEC, n = 7) and a fecal non-pathogenic strain NPEC470 (NPEC, n = 5). Two control groups: phosphate-buffered saline, sham-treated animals ( n = 4) and untreated mice ( n = 8). In addition, segmentation was verified by ex vivo injection of dye into the interstitial spaces of untreated mouse epididymides. Histological findings were compared with specimens from epididymitis patients ( n = 10, age range 14–78, median 60 years) who underwent surgical intervention; control: samples from patients without epididymitis ( n = 16, age range 38–87, median 73 years). PARTICIPANTS/MATERIALS, SETTING, AND METHODS: We investigated the ascending infections by detailed histological analysis in correlation with local infection status in a mouse epididymitis model. As a proof of concept, rare patient material from two archives was analyzed: epididymides from patients who underwent surgical intervention for persisting epididymitis, and for control, histologically normal epididymides from men who underwent orchiectomy for therapy of prostatic carcinoma. MAIN RESULTS AND THE ROLE OF CHANCE: Luminal ascent of E. coli in mice was strictly gated by epididymal segment boundaries. In the mouse model, both strains of E. coli were detected exclusively in the distal cauda segment associated with damage of the epithelium and muscle layer. Ductal constriction occurred in the non-infected upstream segments of infected area, putatively blocking further luminal ascent of bacteria in UPEC-infected animals. Corresponding histological and morphological changes were found in epididymitis patients. The caput region was found to be unaffected in patients and the mouse model. LIMITATIONS, REASONS FOR CAUTION: Patient samples represented advanced cases of epididymitis that made surgical intervention necessary. WIDER IMPLICATIONS OF THE FINDINGS: Our data demonstrate the impact of epididymal segmentation, presumably a protective response mechanism against infectious invasion and bacterial ascent, during epididymitis and affirm the importance of rapid intervention. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by grants from the State of Hessen (LOEWE-MIBIE) and the DFG (KFO 181). The authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: No clinical trial involved.